Crustal Structure of the Niuafo'ou Microplate and Fonualei Rift and Spreading Center in the Northeastern Lau Basin, Southwestern Pacific. Issue 6 (11th June 2020) - Schmid, F.; Kopp, H.; Schnabel, M.; Dannowski, A.; Heyde, I.; Riedel, M.; Hannington, M. D.; Engels, M.; Beniest, A.; Klaucke, I.; Augustin, N.; Brandl, P. A.; et al.
Abstract: The northeastern Lau Basin is one of the fastest opening and magmatically most active back‐arc regions on Earth. Although the current pattern of plate boundaries and motions in this complex mosaic of microplates is reasonably understood, the internal structure and evolution of the back‐arc crust are not. We present new geophysical data from a 290 km long east‐west oriented transect crossing the Niuafo'ou Microplate (back‐arc), the Fonualei Rift and Spreading Center (FRSC) and the Tofua Volcanic Arc at 17°20′S. Our P wave tomography model and density modeling suggest that past crustal accretion inside the southern FRSC was accommodated by a combination of arc crustal extension and magmatic activity. The absence of magnetic reversals inside the FRSC supports this and suggests that focused seafloor spreading has until now not contributed to crustal accretion. The back‐arc crust constituting the southern Niuafo'ou Microplate reveals a heterogeneous structure comprising several crustal blocks. Some regions of the back‐arc show a crustal structure similar to typical oceanic crust, suggesting they originate from seafloor spreading. Other crustal blocks resemble a structure that is similar to volcanic arc crust or a "hydrous" type of oceanic crust that has been created at a spreading center influenced by slab‐derived water at distances <50 km to the arc. Throughout the back‐arc region, we observe a high‐velocity (Vp 7.2–7.5 km s −1 ) lower crust, which is an indication for magmatic underplating, which is likely sustained by elevated upper mantle temperatures in this region. Key Points: First insights into the crustal structure of the northeastern Lau Basin, along a 290 km transect at 17°20′S Crust in southern Fonualei Rift and Spreading Center was created by extension of arc crust and variable amount of magmatism Magmatic underplating is present in some parts of the southern Niuafo'ou Microplate